Analysis and design of DD coupler for dynamic wireless charging of electric vehicles. Issue 2 (22nd January 2018) - Dashora, Hemant Kumar; Buja, Giuseppe; Bertoluzzo, Manuele; Pinto, Rosanna; Lopresto, Vanni
Abstract: In dynamic wireless charging (DWC) of battery-powered electric vehicles (BEVs), inductive power transfer takes place between two coils, one buried into the road and the other one installed onboard BEVs. This paper deals with the design of the coils of a lumped DWC system. At first, the concept of polarized coil is explicated and a DWC-suitable structure of polarized coil, namely the double-D (DD) coil, is illustrated. Then, the paper analyzes the inductive properties of a DD coupler and presents its design for a case study. The design embraces the dimensions of the coils and the magnetic cores, thickness included, and usage of bars instead of plates for the cores in order to save magnetic material. After developing closed-form expressions of the inductive parameters of the coils useful for their preliminary sizing, the analysis and design activities are carried out with the assistance of finite element method codes. Relevant results supporting the design are presented by help of tables, maps, and graphs.